Valores de lactato sérico e sua correlação com parâmetros clínicos de cães saudáveis, mensurados durante atendimento ambulatorial veterinário - Franco, Rodrigo P.; Massufaro, Carla R.; Martineli, Juliana; Girotto, Carolina H.; Hirota, Inajara N.; Zache, Evandro [UNESP]; Hataka, Alessandre [UNESP] (FapUNIFESP (SciELO), 2016)
The measurement of serum lactate is used in the medical routine as a prognosis marker of emergency patients. Its interpretation should not be done disconnectedly from the other clinical parameters once metabolical or environmental stress as well as restraint and/or manipulation of patients can interfere. Thus we tried to measure the levels of serum lactate and clinical parameters of healthy dogs, as their correlation during veterinarian outpatient clinical care. For that we evaluated 80 dogs, males and females, with age ranging from one to eight years, met for polyvalent annual revaccination. We considered to be healthy those dogs that had no clinical events in the last 60 days or alteration in physical exams, blood exam values and serum glycemia. We initially measured body weight, heart rate (HR) and respiratory (RR), capillary refill time, mucosa's coloring, rectal temperature (RT), peripheral temperature (PT) and the difference between RT and PT, Delta T°C. Finally we did the blood exam and the serum glycemia, as well as the serum lactate measurement. For that we used a portable lactimeter, using the blood sample taken from the cephalic vein. Furthermore, when there was correlation between the serum lactate values and the body weight, we divided the dogs according to the calculation of 33 and 66 percentile. Evaluated dogs showed average values of 18.3±12.1 kg of body weight and 3.0±1.9 of age; with HR of 126.6±29.1bpm, RR of 66±24mpm, RT of 38.9±0.4°C, PT of 31.5±1,0°C, Delta T°C of 7.3±1.0°C and serum lactate of 3.2±0.4mmol/L; with the latter showing range of 3.1-3.3mmol/L with 95% of reliability and significant correlation (p < 0.05) between its values and the body weight (r=0.6) and the heart rate (r=0.4). The serum lactate values obtained were compared between the dogs' groups according to their body weight, showing distinguished differences between them. Thereby we concluded that the serum lactate values in dogs under outpatient care is 3.2mmol/L, with a trust gap of 3.1-3.3mmol/L, highlighting the influence that HR and body weight can have on its values.
Serum lactate values and its correlation with clinical parameters evaluated at veterinary ambulatorial exam
Keywords: Clinical parameters; Dogs; Serum lactate